EDLC Type Supercapacitor Electrode Based on Banana Peels Activated Carbon - Alfiatur Rahmah; Ahmad Zainollah; Novi Artika Fitriani; Dwi Sapri Ramadhan; Maf'ud Cahayo; Masruroh Masruroh (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
The objective of this research is to observe the influence of surface area and porosity of banana peels activated carbon on the specific capacitance value as EDLC type supercapacitor electrode. Banana peels have been carbonated at temperature of 600ºC and activated using KOH with concentrations of 5%, 15%, 25% and 35% at temperature of 700ºC. The activated carbon banana peels mixed with PVAc (Polyvinyl acetat), added with aquades and compressed on pressure of 80 kN. The specific capacitance has been carried out using galvanostatic method with KOH 30% as electrolyte solution. Pore size of membrane activated carbon was observed using Scanning Electron Microscopy (SEM) and Brunnuaer-Emmet-Teller (BET) method for surface area of activated carbon. The result shows that the optimum value at activation using KOH 25% with large surface area 540,454 m2/g, porosity 17,89 µm and specific capacitances of 72,93 F/g. The increase of large surface area and porosity activated carbon has affected to specific capacitance value, so activated carbon of banana peels potentials as electrode material supercapacitor  EDLC type. Keyword: activated carbon; porosity; specific capacitance; and supercapacitor electrode.